Evaluation of the Adolescent-Friendly Health Service Program (PKPR) - Wahyuni; Sari Ida Miharti; Lidya Jefra Sofa (CV. CENDIKIA JENIUS INDONESIA, 2025)
Based on the 2024 report, the Airpura Community Health Center experienced various unresolved health issues, one of which was the Adolescent-Friendly Health Service Program (PKPR), with an achievement rate of 36.78%. The purpose of this study is to evaluate the Adolescent-Friendly Health Service Program (PKPR) in the Working Area of Airpura Community Health Center, Pesisir Selatan Regency, in 2025. The research method used is qualitative with a phenomenological design. This study was conducted in the Working Area of Airpura Community Health Center, Pesisir Selatan Regency, from June to September 2025. The informants in this study consisted of the Head of Airpura Health Center, the Head of the Nutrition Unit, one midwife, two PKPR program holders, three community health volunteers (kader), eight adolescents, and eight parents as companions. The results of the study show that the PKPR program at Airpura Health Center still faces challenges in terms of input, including limited human resources, facilities and infrastructure, funding, and suboptimal health promotion. In terms of process, planning and implementation have been carried out with cross-sector involvement; however, they are still hindered by limited time, low adolescent participation, and insufficient parental support. In terms of output, the PKPR program has provided positive impacts in the form of increased knowledge, participation, and healthy behavior among adolescents, although its overall effectiveness remains limited. In conclusion, the PKPR program has been beneficial but remains suboptimal in terms of human resources, facilities and infrastructure, funding, and health promotion. Recommendations to improve the effectiveness of the PKPR program at Airpura Health Center include strengthening the input aspects through enhancing human resources, improving facilities and infrastructure, and optimizing health promotion. In the process aspect, structured planning, efficient implementation time, increased adolescent participation, and stronger parental support are required. From the output perspective, routine evaluation and program innovation are needed to ensure more optimal impacts on adolescent knowledge and healthy behavior.